Diazinon-induced clastogenity and pathological changes in ovaries and testes of clarias gariepinus (2014)
In most tropical developing countries, one of the problems facing aquaculture industry is the pollution of ponds and rivers with pesticides. Chemicals such as diazinon, an organophosphate pesticide, originating from agricultural activity enter the aquatic environment through atmospheric deposition, surface run-off or leaching. Pollutants enter the food chain through accumulation in soft bottom sediment and aquatic organisms. However, information on how these pesticides affect inhabiting organisms is often not available. In a triplicate experimental set-up, seventy-two (72) apparently healthy catfish comprising adult and juvenile of both sexes were therefore exposed to a previously determined no effect concentration (0.405 ppm) of diazinon. Another set of fish was exposed to 0.0625 μg sodium arsenite, a known clastogen, which was used as the positive control, while another set of catfish exposed to the culture water alone was the negative control. Adults and juveniles were exposed separately to avoid cannibalism. After 48 hours of exposure, micronuclei induction was determined in subsets of experimental groups, while exposure continued for 28days. Catfish organs were harvested on days 21 and 28 to determine the effect of long-term exposure to diazinon on histology. Water quality was also monitored before and during exposure in the experimental groups. The result established a significantly high mean micronucleated polychromatic erythrocytes (15.00) in catfish exposed to diazinon suggesting genetic damage (normal is ≤4). The MPE in sodium arsenite exposed fish was 28, while that of the control group was below 4. Effect of sex and age on micronuclei induction was not significant. Histological alteration observed in the ovary and testis was distorted matured cells and extensive testicular degeneration, respectively. The results show that diazinon has clastogenic effect, and may have endocrine disrupting properties because of the histological changes induced in the ovaries and testis.